Marketing Manners of Milk Producing Units-A Case Study of the Purvanchal Region of Uttar Pradesh, India - Chaturvedi, Bhartendu Kr.; Singh, Guru Prasad; Singh, Bhupendra V. (Pakistan Journal of Nutrition, 2009)
Despite the fact that India is the largest producer of milk, the milk producing units are not economically viable. This is substantiated by the fact that usually milk producers do not grow wealthy as manufacturers do. The researches in the area, generally aim at breed improvement, feeding, milking, animal health care, etc. the economic aspect of researches generally evaluate cost and benefits. However, the failure lies in the milk marketing. The present paper endeavors to capture the marketing manners of milk producing units of the Purvanchal region of Uttar Pradesh India based on a sample of size 280 drawn randomly from the region using a questionnaire. The questionnaire contained, besides general information such as yearly value of milk, number of animals and their diet, questions regarding marketing that included type of marketing. Order getting cost, product differentiations and differentiation cost, type of advertisement and cost and method of physical distribution and cost. It is found that there are miles to go in the direction of marketing. People are generally not aware of the fact that marketing can add to the performance. They have no marketing strategies. Marketing variables are playing negative role in determination of value of output. The significant variable that emerges in such determination is the quantity of output.